T-TUBE ENTEROSTOMY: TECHNICAL CONSIDERATIONS AND CLINICAL APPLICATIONS - P. Stamov; S. Stamova; N. Ermenlieva; E. Georgieva (Trakia Journal of Sciences)
Introduction: T-tube enterostomy is a minimally invasive technique for temporary gastrointestinal decompression in pediatric patients, particularly neonates and infants. Traditional enterostomy methods often lead to complications and prolonged recovery, highlighting the need for alternative approaches. Materials and methods: This study evaluates the outcomes of 33 patients under one year of age who underwent T-tube enterostomy at St. Anna Hospital, Varna (2008–2021). The cohort included neonates with low birth weight and gastrointestinal conditions, such as bowel obstruction, meconium ileus, and necrotizing enterocolitis.